The Diagnosis of Traumatic Brain Injury on the Battlefield - Schmid, Kara; Tortella, Frank C. (Frontiers in Neurology, 2012)
The conflicts in Iraq and Afghanistan have placed an increased awareness on traumatic brain injury (TBI). Various publications have estimated the incidence of TBI for our deployed servicemen, however all have been based on extrapolations of data sets or subjective evaluations due to our current method of diagnosing a TBI. Therefore it has been difficult to get an accurate rate and severity of deployment related TBIs, or the incidence of multiple TBIs our service members are experiencing. As such, there is a critical need to develop a rapid objective method to diagnose TBI on the battlefield. Because of the austere environment of the combat theatre the ideal diagnostic platform faces numerous logistical constraints not encountered in civilian trauma centers. Consequently, a simple blood test to diagnosis TBI represents a viable option for the military. This perspective will provide information on some of the current options for TBI biomarkers, detail concerning battlefield constraints and a possible acquisition strategy for the military. The end result is a non-invasive TBI diagnostic platform capable of providing much needed advances in objective triage capabilities and improved clinical management of in-Theatre TBI.